The history of fever, leukocytic pyrogen and interleukin-1 - Dinarello, Charles A (Temperature (Austin), 2015)
There has been great progress in the 30 y since the reporting in 1984 of the cDNA for interleukin1 (IL1) β in the human and IL1α in the mouse. However, the history of IL1 begins in the early 1940s with investigations into the nature of an endogenous fever-producing protein released rabbit peritoneal neutrophils. Most researchers in immunology today are unaware that the field of cytokines, particularly the field of inflammatory cytokines. Toll-like receptors and innate immunity traces back to studies on fever. Researchers in infectious diseases wanted to know about an endogenous protein that caused fever, independent of infection. The endogenous fever-producing protein was called by various names: granulocyte, endogenous or leukocytic pyrogen. It is a fascinating and sometimes controversial story for biology and medicine and for the treatment of inflammatory diseases. Few imagined that this fever-producing protein would play such a major role in nearly every cell and in most diseases. This paper reviews the true background and milestones of interleukin1 from the purification of leukocytic pyrogen to the first cDNA of IL1β and the validation of cytokine biology from ill-defined factors to its present day importance.